Using Word Wall Website As A Strategy To Improve Students’ Vocabulary Mastery - Umar Umar; Rosnani Abdul Rahman; Pujalinda Mandarsari; Mawarwati Mawarwati; Syaifuddin Amir (Journal on Education, 2023)
Vocabulary is one of important aspect before learning skill of English. Because of the students lack of vocabulary, the teacher should use a strategy to solve the problem. One of the strategies is using word wall website. This research aims to know the significant influence between the use of word wall website improve students’ vocabulary mastery. This research is done by using quantitative method with quasi experimental design. From the data analysis computed by using SPSS, then as the basis for decision that h0 is rejected and h1 is accepted. Based on the result of the research that has been done by the writer, the researcher concluded that using word wall website has a significant effect in improving students’ vocabulary mastery.